CH3NH3PBI3 IV Output Parameters Degradation Investigation - M.N. Orlova; S.I. Didenko; D.S. Saranin; O.I. Rabinovich; A.Y. Krukov; A.V. Kolesnikov (Журнал нано- та електронної фізики)
Organic photovoltaics, based on hybrid inorganic organic optoelectronic perovskites, with structure alkali- metal- halide are the newest emerging technology in the third generation development. Despite tremendous efficiency records, more than 21 %, optoelectronic perovskites’ instability prevents their commercialization and mass production. Issues with degradation are caused by various types of environmental influences. The main issues with stability and power loss in devices are linked to moisture, oxygen, temperature, and light-induced structure defects. Initial measurements are taken after long term debugging with minimal aggressive exposure to environmental conditions. In this case, preliminary degradation studies begin from measurements of light-induced effects. In this work, we will present the main trends in degradation of external characteristics during common I-V measurements, in the order of parameters which were effected the least by environmental factors. This investigation was made on fixed CH3NH3PBI3 solar cells with standard 1.5 AM testing and initial efficiencies more than 8 %.